PENGARUH CONTENT MARKETING TERHADAP PURCHASE INTENTION YANG DIMEDIASI OLEH TRUST - Kevin Septian Wiryadharma, Putu; Ayu Tirtayani, I Gusti (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Digital transformation has fundamentally reshaped marketing paradigms, positioning content marketing as a key strategy for building meaningful relationships between brands and consumers. This study aims to analyze the effect of content marketing on purchase intention with trust as a mediating variable among male TikTok users in Denpasar City who are aware of the RUCAS fashion brand. This research employs a quantitative approach with a purposive sampling technique involving 100 qualified respondents. Data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The findings reveal that content marketing has a positive and significant effect on trust (t = 12.747; p < 0.05), trust positively affects purchase intention (t = 2.512; p < 0.05), and content marketing also positively affects purchase intention (t = 4.052; p < 0.05). Furthermore, trust partially mediates the relationship between content marketingand purchase intention, with a VAF value of 61.95%. The R² value for trust is 0.588 and for purchase intention is 0.506, while the Q² value of 0.797 indicates a strong model fit. These results highlight that authentic, relevant, and consistent content marketing strategies can effectively build consumer trust, ultimately increasing purchase intentions. Theoretically, this study reinforces the application of the Stimulus–Organism–Response (S-O-R) theory in digital marketing contexts, while practically providing insights for local brands to develop trust-based content marketing strategies as a foundation for improving purchase conversion.